Answer:
-4
Step-by-step explanation:
2-26=-24
-24-(-20) basically says -24+20=-4
Answer:
The constant of proportionality k is given by k=y/x where y and x are two quantities that are directly proportional to each other. Once you know the constant of proportionality you can find an equation representing the directly proportional relationship between x and y, namely y=kx, with your specific k.
Answer:
B
Step-by-step explanation:
Answer:
5
Step-by-step explanation:
26 × 10 ÷ 100 = 52 · x ÷ 100
260 = 52 · x
x = 5
The information shown here only shows a principal sum, a rate of interest and a period or time. There is no question as to what is needed. But suppose the need is for simple interest, then we calculate using the given information and the formula:
I = PRT
where I is simple interest, P is the principal, R is the rate per year, and T is time
P = 290, T is 6 months which is 0.5 years, R = 12.5 % which is written as 0.125 in decimal fraction.
I = 290 × 0.125 x 0.5 → I = 18.125
Therefore after 6 months , the interest earned will be 18. 125 dollars